PENDAYAGUNAAN CANGKANG BASAH EX HYDROCYCLONE PABRIK KELAPA SAWIT PT. PALMINDO MITRA LESTARI UNTUK PEMBANGKIT LISTRIK TENAGA BIOMASSA - Muhamad Samsir; Wahri Sunanda; Asmar Asmar (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2015)
This study aims to determine the potential of biomass electricity generated from the shell the rest of the production of palm oil mill PT. Palmindo Mitra Lestari. By converting the value of the availability of shells obtained within one hour of production with a calorific value of 23569.2595 kJ / kg and converted to 3,600,000 kJ / h = 1 MW to get the value of the power generated. The potential power output if the operating hours of the system clock generator adapted to production amounted to 13,660 MW. Average potential power that can be generated from the production of eggshell during 2013 Ex Hydrocyclone if the generating system operates 24 hours non-stop to reach 8.972 MW each hours.